Cycle road racing - Newman, Tom
Cycle Road Racing provides a practical and instructional guide for those entering into cycle road racing, and those improving their performance. It covers the latest developments in racing and cycle technology, and guides the reader through all stages of racing, from setting up the bike correctly to race da itself. The book includes materials on: Clothing, equipment and setting up your bike; Training, including the use of turbo training in winter and sample training plans; Techniques such as cornering, climbing and descending; Avoiding injury and recovery after injury; Nutrition; In-depth coverage of time trials and veterans racing ; Computerization of racing, such as use of sat navs and computerized training aids. Cycle Road Racing will be essential reading for racers looking to improve their skills, club riders and coaches